PENERAPAN MODEL PEMBELAJARAN SSCS (SEARCH, SOLVE, CREATE, SHARE) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS XI PADA MATERI KALOR - Permata, Aulia; Irianti, Mitri; Yennita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the SSCS (Search, Solve, Create, Share) learning model on the problem-solving abilities of eleventh-grade students in the heat topic. The research method used was quantitative with a quasi-experimental design in the form of a posttest-only control group design. The study sample consisted of two classes: the experimental class taught using the SSCS model and the control class taught using conventional learning. The research instrument used was a problem-solving ability test in the form of descriptive questions given at the end of the lesson (posttest). Data were analyzed using normality tests, homogeneity tests, and independent sample t-tests. The results showed a significant difference between the problem-solving abilities of students in the experimental and control classes, with a significance value of <0.05. Thus, the application of the SSCS (Search, Solve, Create, Share) learning model has an effect on improving the problem-solving abilities of eleventh-grade students in the heat topic